SIMSIZ TARMOQ TEXNOLOGIYALARI ORQALI O’LCHASH NATIJALARINI MASOFADAN BOSHQARISHNI TASHKIL ETISH EVALYUTSIYASI - Akhmadaliyev Anvarbek Alijon o’g’li (Journal of new century innovations, 2022)
CDMA (Code Division Multiple Access), GSM (Global Systems for Mobile Communications), TDMA (Time Division Multiple Access), 802.11, WAP (Wireless Application Protocol) wireless technology protocol), 3G and 4G (third and fourth generation technologies), GPRS (General Packet Radio Service, data packet transmission service), Bluetooth (medium and short distance network), EDGE (Enhanced Data) Rates for GSM Evolution, improved GSM network).